FEAR OF PAIN IN NURSING AND MIDWIFERY STUDENTS: A CROSS- SECTIONAL STUDY: Hemşirelik ve Ebelik Öğrencilerinde Ağrı Korkusu - ÖZDEMİR, AYSUN; GÜNER, Şükriye İlkay (Göbeklitepe Medical Science Journal, 2024)
This study was conducted to determine the pain fears of midwifery and nursing students who studying at the faculty of health sciences. The population of the cross-sectional study consisted of 1430 students who continued their active education at the faculty of health sciences of a state university in the 2020-2021 academic year. With power analysis, the sample size was calculated as 633 and the stratified sampling method was used in sample selection. Research data was collected between November 2020 and February 2021, and "Personal Information Form" and "Fear of Pain Scale-III" forms were used as data collection tools. The data were evaluated in the SPSS 23.0 statistical package program. Percentage, frequency, mean, standard deviation, independent groups t-test and correlation tests were used in the analysis of the data. The average age of the participants was 20.7±1.54 and 73.9% were from the nursing department and 26.1% were from the midwifery departmen. The total score averages of the scale sub-dimensions of the students; the fear of severe pain was 31.46±8.25, the fear of mild pain was 23.89±6.68, the fear of medical pain was 26.18±7.69, and the mean total score of the scale was 81.52±20.03. A high negative relationship was found between age and total score, and a weak negative relationship was found with fear of mild pain. A weak negative relationship was found between gender and all subscales and the total score. It was determined that the students' fear of pain levels were at a medium level and there was a negative relationship between gender and age. In order to reduce the fear of pain, it is recommended that pain-related training be given in comprehensive groups.